Corpus oraux, liaison et locuteurs non natifs: de la recherche en phonologie à l'enseignement du français langue étrangère - Racine, Isabelle; Detey, Sylvain (My University, 2015)
This paper focuses on the acquisition of L2 French liaison. First we present the challenges that liaison involves in L1 and in L2. Then we introduce the methodological framework in which the seven studies included in the present volume have been carried out: the ʺInterphonologie du français contemporainʺ project (IPFC), which stands as the non-native part of the PFC project (ʺPhonologie du français contemporainʺ), a large sociophonological survey of the pronunciation of French in the Frenchspeaking world. IPFC aims at compiling and analyzing a large database of oral French produced by learners with different L1s on the basis of a single survey protocol. We briefly present the methodology used in the project and we focus on L2 liaison, with a description of the alphanumeric code designed for its treatment. This common methodology has been applied to all of the IPFC data, as is illustrated in the seven papers presented in this volume. This work will enrich our knowledge of L2 liaison and should contribute in the long term to a renewal of the pedagogical material used for teaching L2 French.
Keywords: liaison; consonant linking; external sandhi; French as Foreign Language; oral French; learner corpora; InterPhonologie du Français Contemporain (IPFC); L2 phonological acquisition